Assessment of Solid Waste Management Methods in Some Selected Parts of Owerri West, Imo State, Nigeria - J. U. Udensi; C. O. Anyanwu; M. C. Opara; C. C. Duru; E. C. Onyima; J. C. Okafor (Archives of Current Research International, 2023)
In many developing countries, improper solid waste management (SWM) poses serious environmental and public health risks. Solid wastes are typically dumped into drains and open areas since they are not collected. The effects of this incident affect both human life and the environment. In addition to identifying sources, types, and defining features of solid waste in the study region, this study aimed to evaluate the current solid waste management methods in three host communities (Eziobodo, Obinze, and Ihiagwa) of the Federal University of Technology Owerri, Imo state, Nigeria. A systematic questionnaire was used to collect data for the cross-sectional descriptive study. Four hundred and four (404) copies of the questionnaire were distributed, and a multi-stage sampling procedure was adopted for the selection of respondents and subsequent data collection. The data generated were presented in tables in percentages and were analyzed using the Statistical Package for Social Science (SPSS) version 22.0. Results obtained from this study show that 52.7% of the respondents were female while 47.3% are male. The age range was between 26 and 35 years. Considering the pattern of waste management practice, the majority of the respondents practice incineration (42.8%), this was followed by recycling (35.9%), and fermentation (11.6%) while composting (9.7%) was the least practiced waste management pattern. Garbage 42.8%, plastics 35.9%, cans 11.6%, and paper 9.7% were the types of solid wastes obtained from this study. The majority of the respondents (42.3%) disposes of waste by themselves while Government/paid collectors constitute only 2.0% of waste disposal method. About 55.4% of the waste is dumped in the gutter/drains, while 34.7%, 5.7%, and 4.2% of the waste are disposed of at nearby bushes, roadsides, and approved dumpsites respectively. The major factor associated with the improper waste disposal method as reported by the majority of respondents 71% (286) was lack of information. According to the study, there is a significant relationship between access to waste dumpsites and environmental sustainability (p= 0.022). There is a need for government to equip rural areas with facilities to dispose of refuse and also place them at a close interval apart from the households so that they can be easily accessed as well as train local residents about how solid waste affects human and environmental health.